2016
DOI: 10.1111/bjc.12104
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic motivation as a mediator between metacognition deficits and impaired functioning in psychosis

Abstract: The cross-sectional design of this study is a limitation, and additional longitudinal studies are needed to confirm the direction of the findings and rule out rival hypotheses. Generalization of the findings may be limited by the sample composition. It may be that different relationships exist between metacognition, intrinsic motivation, and functioning in those with early psychosis or among those in an acute phase or who decline treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 83 publications
2
28
0
1
Order By: Relevance
“…These findings are consistent with prior analyses and studies that identified whether on average, higher levels of metacognition lead to higher levels of motivation in people with schizophrenia (Luther et al, 2016a; Luther et al, 2016b; Tas et al, 2012; Vohs et al, 2014). Notably, our findings build on these prior studies by identifying the specific level of metacognition necessary to enable high motivation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with prior analyses and studies that identified whether on average, higher levels of metacognition lead to higher levels of motivation in people with schizophrenia (Luther et al, 2016a; Luther et al, 2016b; Tas et al, 2012; Vohs et al, 2014). Notably, our findings build on these prior studies by identifying the specific level of metacognition necessary to enable high motivation.…”
Section: Discussionsupporting
confidence: 91%
“…Included participants had a mean age of 48.67 ( SD = 9.90) and were primarily male ( n = 153, 87%) and African American ( n = 97, 55%) with an average of 12.74 ( SD = 2.12 ) years of education. Of note, although we have previously presented regression-based analyses with metacognition and motivation (Luther et al, 2016b), this is the first study to explicitly test whether specific levels of metacognition are needed for motivation to emerge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work, including our own, has shown significant interrelationships between motivation and cognitive test performance (Choi, Choi, Felice Reddy, & Fiszdon, 2014;Fervaha, Siddiqui, Foussias, Agid, & Remington, 2015;Fervaha, Zakzanis, et al, 2014;Gard, Fisher, Garrett, Genevsky, & Vinogradov, 2009;Luther, Firmin, Vohs, & Buck, 2016;Nakagami, Xie, Hoe, & Brekke, 2008). Two studies using personality assessments of trait motivation in schizophrenia have, however, failed to find a significant relationship with cognitive performance in this population (Barch et al, 2008;Choi et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
“…One possible explanation may be found in case reports detailing a very long course of treatment (32 months; Lysaker et al ., , 5 years; Buck & George, ) where the first changes in understanding the Other are found only after 16 months of psychotherapy. With disturbances in self‐experience frequently considered central to schizophrenia (Andresen, Oades, & Caputi, ; Hasson‐Ohayon, Goldzweig, Lavi‐Rotenberg, Luther, & Lysaker, ; Hasson‐Ohayon et al ., ; Hasson‐Ohayon, Mashiach‐Eizenberg, Lysaker, & Roe, ; Kukla, Lysaker, & Salyers, ; Luther et al ., ), it is possible that increases in Self‐Reflectivity are the first stage of improvement, as it allows one to develop motives for change and take responsibility over the process of changing (Hasson‐Ohayon et al ., ).…”
Section: Discussionmentioning
confidence: 99%